(untitled) (The Gaze: Journal of Tourism and Hospitality, 2022)
A key challenge still exists for emancipation of women in the tourism industry in Nepal. The research addresses how females in Nepal transform themselves through engagement with trekking in remote areas. The authors investigated a female only tourism enterprise to determine how women can encounter avenues to reliable income support. Interviewees were members of Empowering Women Nepal (EWN), a Nepali Non-Government Organisation (NGO), and their interviews were used as a case study regarding women’s training. Open ended questions focused on the background of women who are likely to engage with tourism, barriers preventing engagement in tourism, the positive and negative side to tourism, avenues of support, and specific outcomes to date. The research found that rural and remote Nepali women are being emancipated via engagement with tourism.